External Validation of the United Kingdom Transplant Benefit Score in Australia and New Zealand. (March 2023) - Lee, Eunice G.; Perini, Marcos V.; Makalic, Enes; Oniscu, Gabriel C.; Fink, Michael A.
Introduction: In Australia and New Zealand, liver allocation is needs based (based on model for end-stage liver disease score). An alternative allocation system is a transplant benefit-based model. Transplant benefit is quantified by complex waitlist and transplant survival prediction models.Research Questions: To validate the UK transplant benefit score in an Australia and New Zealand population.Design: This study analyzed data on listings and transplants for chronic liver disease between 2009 and 2018, using the Australia and New Zealand Liver and Intestinal Transplant Registry. Excluded were variant syndromes, hepatocellular cancer, urgent listings, pediatric, living donor, and multi-organ listings and transplants. UK transplant benefit waitlist and transplant benefit score were calculated for listings and transplants, respectively. Outcomes were time to waitlist death and time to transplant failure. Calibration and discrimination were assessed with Kaplan–Meier analysis and C-statistics.Results: There were differences in the UK and Australia and New Zealand listing, transplant, and donor populations including older recipient age, higher recipient and donor body mass index, and higher incidence of hepatitis C in the Australia and New Zealand population. Waitlist scores were calculated for 2241 patients and transplant scores were calculated for 1755 patients. The waitlist model C-statistic at 5 years was 0.70 and the transplant model C-statistic was 0.56, with poor calibration of both models.Conclusion: The UK transplant benefit score model performed poorly, suggesting that UK benefit-based allocation would not improve overall outcomes in Australia and New Zealand. Generalizability of survival prediction models was limited by differences in transplant populations and practices.